Pancasila sebagai Dasar Negara Indonesia - Syafrida, Meyli; Novita, Tri Reni (VISA: Journal of Vision and Ideas, 2025)
The basis of the state is a series of values extracted from and growing in Indonesian society itself since centuries ago, which contains ideas about the ideals of the state (staatsidee) and the ideals of law (rechtsidee) so that it is used as a source for the preparation of basic law or articles of the Constitution. Pancasila is the philosophical basis of the Indonesian state which was proposed by Ir. Soekarno on June 1, 1945, and was formalized as the basis of the state on August 18, 1945. The five basic principles of Pancasila are Belief in One God, Fair and civilized humanity, Indonesian Unity, Democracy led by wisdom in deliberation and representation, and Social justice for all Indonesian people.